2014
DOI: 10.2147/jpr.s47005
|View full text |Cite
|
Sign up to set email alerts
|

Pain control following inguinal herniorrhaphy: current perspectives

Abstract: Inguinal hernia repair is one of the most common surgeries performed worldwide. With the success of modern hernia repair techniques, recurrence rates have significantly declined, with a lower incidence than the development of chronic postherniorrhaphy inguinal pain (CPIP). The avoidance of CPIP is arguably the most important clinical outcome and has the greatest impact on patient satisfaction, health care utilization, societal cost, and quality of life. The etiology of CPIP is multifactorial, with overlapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 125 publications
0
22
0
Order By: Relevance
“…Systematic reviews published within the last decade have generally found similar predictors for CPIP development. 104 , 146 , 151 , 152 The International Endohernia Society guidelines summarized from the literature: young age, female gender, preoperative pain level, and postoperative pain intensity as risk factors for chronic postoperative pain. 104 One author has summarized risk factors for postherniorrhaphy inguinal pain (Table 3).…”
Section: Pain: Prevention and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews published within the last decade have generally found similar predictors for CPIP development. 104 , 146 , 151 , 152 The International Endohernia Society guidelines summarized from the literature: young age, female gender, preoperative pain level, and postoperative pain intensity as risk factors for chronic postoperative pain. 104 One author has summarized risk factors for postherniorrhaphy inguinal pain (Table 3).…”
Section: Pain: Prevention and Treatmentmentioning
confidence: 99%
“…One emphasized the complexity of, and the need for individualization in, treatment schemes making definitive broadly applicable treatment algorithms difficult to compose. 152 The other concluded that while neurectomy provides the best results, improved studies with long-term outcome measures should be initiated. 234 …”
Section: Pain: Prevention and Treatmentmentioning
confidence: 99%
“…One of the applications of TAs is in hernia surgery, where tissue adhesives are used to fix prosthetic materials. The use of sutures for the same purpose, both absorbable and nonabsorbable, has been subject to clinical reviews because some patients report postoperative pain, which has been attributed to nerve entrapment caused by the sutures themselves [ 8 ]. In clinical practice, some authors [ 13 , 25 , 26 ] have reported better comfort and less postoperative pain after hernioplasty using tissue adhesives to fix the mesh.…”
Section: Discussionmentioning
confidence: 99%
“…Sutures have been associated with the appearance of clinical symptoms of pain both in the postoperative period and in the long term, in patients undergoing inguinal hernia [ 6 , 7 ]. The phenomenon of nerve entrapment is among the possible causes of postoperative pain [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods to reduce the occurrence of inguinodynia have been suggested which include prophylactic ilioinguinal neurectomy, laparoscopic TEP repair, use of lightweight meshes and use of fibrin glue sealant for mesh fixation has been described [19][20][21].…”
Section: Review Of Literaturementioning
confidence: 99%